A method for preparing a hydrogel electrolyte with a wide voltage window by polyacid regulation

By using phosphotungstic acid in hydrogel electrolytes to disperse in polymer cross-linking networks, the problems of low energy density and narrow voltage window of existing hydrogel electrolytes are solved, and a wide voltage window and high ionic conductivity hydrogel electrolytes are realized, suitable for all-solid supercapacitors.

CN115938816BActive Publication Date: 2025-03-14ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211635486.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-19
Publication Date
2025-03-14
Estimated Expiration
2042-12-19

AI Technical Summary

Technical Problem

The low decomposition voltage of existing hydrogel electrolytes leads to low energy density and few studies have been conducted to broaden the voltage window. Common strategies have the disadvantages of low ionic conductivity and flammability and toxicity.

Method used

By selecting phosphotungstic acid as a heteropolyacid and dispersing it in the crosslinking network of the polymer, PVA-PEG-PW12 hydrogel electrolyte is prepared, using the high hydrogen analysis reaction overpotential and "proton sponge" characteristics of PW12 to broaden the voltage window and ensure high ionic conductivity.

Benefits of technology

It realizes a wide voltage window (up to 1.7V) and high proton conductivity (up to 51.7S·cm-1) of hydrogel electrolytes, while maintaining excellent mechanical properties and safety, and is suitable for all-solid state supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115938816B_ABST
    Figure CN115938816B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a hydrogel electrolyte with a wide voltage window by regulating a polyacid, wherein phosphotungstic acid is dispersed in a matrix of polyvinyl alcohol-polyethylene glycol to prepare PW 12 ‑PVA‑PEG‑hydrogel electrolyte, using PW 12 The higher hydrogen evolution reaction overpotential can broaden the voltage window of the electrolyte, while using PW 12 The "proton sponge" property of the gel electrolyte is used to ensure high ionic conductivity, while also extending the mechanical properties. This method has a simple preparation process, high material preparation repeatability, low equipment requirements, and the chemicals used are cheap and readily available, so it has broad prospects in industrial applications.
Need to check novelty before this filing date? Find Prior Art

Description

(I) Technical field

[0001] The invention relates to a method for preparing a hydrogel electrolyte with a wide voltage window by regulating polyacids. (II) Background technology

[0002] In recent years, the application demand for flexible energy storage devices in wearable devices, implantable medical devices, flexible displays and other fields has been growing. As a new type of energy storage device, flexible all-solid-state supercapacitors have attracted close attention from scientists due to their advantages such as fast charging and discharging rates, good deformability and long cycle life. Current flexible all-solid-state supercapacitors usually use gel electrolytes, which mainly include three categories: hydrogels, organic gels and ionic liquid gels. Among them, hydrogel electrolytes have the advantages of high conductivity, environmental friendliness, low cost and good stability, and have very good application prospects. However, the low decomposition voltage of hydrogel electrolytes makes it have a major defect of low energy density. The development of hydrogel electrolytes with a wide voltage window, high ionic conductivity and excellent mechanical properties is an important problem that needs to be solved urgently in this field.

[0003] At present, the main research on hydrogel electrolytes is focused on improving their mechanical properties, water retention, deformability and / or conductivity, while relatively few studies have been conducted on broadening the working voltage window of hydrogel electrolytes. The most commonly used strategy is to enhance other components in the electrolyte, such as organic electrolytes or ionic liquids. Although this type of hydrogel electrolyte with a wide voltage window can provide a wide voltage window of more than 2V, it usually has the disadvantages of low ionic conductivity and flammability and toxicity, which leads to poor electrochemical performance. (III) Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a hydrogel electrolyte having a wide voltage window by adjusting a polyacid. 12 O 40 , abbreviated as PW 12 , which is a common heteropoly acid) is dispersed in a cross-linked network of a polymer (the present invention uses a cross-linked network formed by polyvinyl alcohol (PVA) and polyethylene glycol (PEG) to prepare PVA-PEG-PW 12 Hydrogel electrolyte, using PW 12 The higher hydrogen evolution reaction overpotential can broaden the voltage window of the electrolyte, while using PW 12 The "proton sponge" property of the gel electrolyte is used to ensure high ionic conductivity. The method is simple in preparation process, easy to operate, highly safe, and is conducive to large-scale production.

[0005] Compared with other similar materials, the hydrogel electrolyte prepared by this method has a wide voltage window (up to 1.7V) and can ensure its high proton conductivity (up to 51.7S·cm -1 ), and a high elongation at break of 996%, showing excellent performance in the application of all-solid-state supercapacitors.

[0006] To achieve the purpose of the present invention, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a hydrogel electrolyte with a wide voltage window by polyacid regulation, the method comprising the following steps:

[0008] (1) dissolving polyvinyl alcohol (PVA) and polyethylene glycol (PEG) in an acidic solvent to obtain a PVA-PEG mixed solution;

[0009] (2) Phosphotungstic acid (H3PW 12 O 40 , abbreviated as PW 12 ) is dissolved in an acidic solvent to obtain PW 12 Solution;

[0010] (3) PW 12 The solution was slowly added dropwise to the PVA-PEG mixed solution, heated to 80-90°C and stirred at constant temperature to obtain PVA-PEG-PW 12 Solution

[0011] (4) Slowly add the citric acid aqueous solution to the PVA-PEG-PW 12 The solution was stirred and mixed, and the temperature was maintained at 80-90°C; the obtained solution was poured into a mold and vacuum dried to obtain PVA-PEG-PW 12 The hydrogel electrolyte is the hydrogel electrolyte with a wide voltage window.

[0012] The polyvinyl alcohol is preferably PVA-1788, with a degree of alcoholysis of 87-89%.

[0013] The molecular weight of the polyethylene glycol is preferably 600-20000.

[0014] In the step (1), the PVA-PEG mixed solution is preferably prepared at a temperature of 75-85°C.

[0015] In the step (2), PW is preferably prepared at a temperature of 30-50 °C. 12 Solution.

[0016] The acidic solvent in step (1) and step (2) is preferably a 1-3 mol / L sulfuric acid solution, more preferably a 2 mol / L sulfuric acid solution.

[0017] In the step (1), the mass ratio of the polyvinyl alcohol to the polyethylene glycol is preferably 1:0.2-1, more preferably 1:0.3-0.5.

[0018] In the step (1), the volume amount of the acidic solvent is preferably 2 to 10 mL / g, more preferably 5 mL / g, based on the mass of the polyvinyl alcohol.

[0019] In the step (2), the volume amount of the acidic solvent is preferably 30 to 250 mL / g, more preferably 50 to 200 mL / g, based on the mass of phosphotungstic acid.

[0020] In the step (2), the mass ratio of phosphotungstic acid to polyvinyl alcohol is 0.0025 to 0.015:1, preferably 0.0025 to 0.01:1, and more preferably 0.0075:1.

[0021] Preferred PW 12 The volume ratio of the solution to the PVA-PEG mixed solution is 1:8 to 12, more preferably 1:10.

[0022] The stirring time in step (3) is preferably 2 to 4 hours.

[0023] The stirring time of step (4) is preferably 20 to 40 minutes.

[0024] In the step (4), the citric acid, PVA-PEG-PW 12 The preferred mass ratio of polyvinyl alcohol in the solution is 0.05 to 0.1:1, preferably 0.08 to 0.9:1.

[0025] In the step (4), the concentration of citric acid in the citric acid aqueous solution is preferably 0.3 to 0.5 g / mL.

[0026] In the step (4), the vacuum drying is preferably carried out in a vacuum drying oven at 50-70° C. for 3-6 hours.

[0027] The present invention also provides a hydrogel electrolyte with a wide voltage window prepared by the above method.

[0028] The hydrogel electrolyte with a wide voltage window provided by the present invention can be used to prepare an all-solid-state supercapacitor.

[0029] PVA-PEG-PW provided by the present invention 12 The technical advantages of the preparation method of hydrogel electrolyte are mainly reflected in:

[0030] (1)PW 12 It has a high hydrogen evolution reaction overpotential, which can inhibit the water decomposition reaction to expand the PVA-PEG-PW12 The voltage window of the hydrogel electrolyte can be as high as 1.7V.

[0031] (2) PW 12 It has the common property of polyacid compounds as "proton sponge", which effectively ensures the 12 High proton conductivity of hydrogel electrolytes, with conductivity up to 51.7 S·cm -1 .

[0032] (3)PW 12 It can be dispersed in the network structure of the PVA-PEG polymer matrix through hydrogen bonding, thereby improving the mechanical properties of the hydrogel electrolyte, with an elongation at break of up to 996%.

[0033] (4) The prepared hydrogel electrolyte is applied in all-solid-state supercapacitors and exhibits excellent performance.

[0034] (5) Preparation of PVA-PEG-PW 12 The process of hydrogel electrolyte is simple, easy to operate, highly safe, has low equipment requirements, and the chemicals used are cheap and easily available, which is conducive to large-scale production and has broad prospects in industrial applications. (IV) Description of the drawings

[0035] Figure 1 PVA-PEG-PW prepared in Example 3 12 Optical image of a conductive hydrogel electrolyte.

[0036] Figure 2 PVA-PEG-PW prepared in Example 3 12 SEM image of the hydrogel electrolyte.

[0037] Figure 3 PVA-PEG-PW prepared in Example 3 12 EDS image of the hydrogel cross section.

[0038] Figure 4 Comparison chart of CV curve and GCD curve of the prepared PVA-PEG conductive hydrogel.

[0039] Figure 5 PVA-PEG-PW prepared in Example 1 12 Electrochemical performance diagram of gel electrolyte samples.

[0040] Figure 6 PVA-PEG-PW prepared in Example 2 12 Electrochemical performance diagram of gel electrolyte samples.

[0041] Figure 7PVA-PEG-PW prepared in Example 3 12 Electrochemical performance diagram of gel electrolyte samples.

[0042] Figure 8 PVA-PEG-PW prepared in Example 4 12 Electrochemical performance diagram of gel electrolyte samples.

[0043] Fig. 9 PVA-PEG-PW prepared in Example 1-4 12 Ionic conductivity diagrams and corresponding column distribution diagrams of gel electrolyte samples and PVA-PEG hydrogel samples, where Figure a is the ionic conductivity diagram and Figure b is the column distribution diagram.

[0044] Fig.10 PVA-PEG-PW prepared in Examples 2, 3 and 4 12 Stress-strain curves of gel electrolyte samples and PVA-PEG hydrogel samples. (V) Specific implementation methods

[0045] The technical solution of the present invention is further described below with reference to specific embodiments, but the protection scope of the present invention is not limited thereto.

[0046] The PVA used in the examples is PVA-1788, with a degree of alcoholysis of 87-89%.

[0047] The molecular weight of the polyethylene glycol used was 20,000.

[0048] Example 1

[0049] (1) Dissolve 4.0 g PVA and 1.3 g PEG in 10 mL sulfuric acid solution (2 mol / L) respectively, then mix the two solutions evenly and heat to 80° C. to obtain 20 mL of PVA-PEG solution;

[0050] (2) 10 mg PW 12 Dissolve in 2 mL of sulfuric acid solution (2 mol / L) and heat to 50°C, then slowly dropwise add it to the PVA-PEG solution obtained in step (1) and stir at 80°C for 2 hours to obtain PVA-PEG-PW 12 Solution;

[0051] (3) Dissolve 0.35 g of citric acid in 1 mL of deionized water and slowly add it dropwise to the PVA-PEG-PW obtained in step (2). 12 The solution was stirred at 80°C for 30 minutes and then the mixed solution was poured into a surface dish. The mold was then placed in a vacuum drying oven and dried at 50°C for 5 hours. After cooling, PVA-PEG-PW was obtained. 12-1 hydrogel electrolyte.

[0052] Example 2

[0053] (1) Dissolve 4.0 g PVA and 1.3 g PEG in 10 mL sulfuric acid solution (2 mol / L) respectively, then mix the two solutions evenly and heat to 80° C. to obtain 20 mL of PVA-PEG solution;

[0054] (2) 20 mg PW 12 Dissolve in 2 mL of sulfuric acid solution (2 mol / L) and heat to 50°C, then slowly dropwise add it to the PVA-PEG solution obtained in step (1) and stir at 80°C for 2 hours to obtain PVA-PEG-PW 12 Solution;

[0055] (3) Dissolve 0.35 g of citric acid in 1 mL of deionized water and slowly add it dropwise to the PVA-PEG-PW obtained in step (2). 12 The solution was stirred at 80°C for 30 minutes and then the mixed solution was poured into a surface dish. The mold was then placed in a vacuum drying oven and dried at 50°C for 5 hours. After cooling, PVA-PEG-PW was obtained. 12 -2 hydrogel electrolyte.

[0056] Example 3

[0057] (1) 4.0 g PVA and 1.3 g PEG were respectively dissolved in 10 mL sulfuric acid solution (2 mol / L), and then the two solutions were evenly mixed and heated to 80° C. to obtain 20 mL of PVA-PEG solution;

[0058] (2) 30 mg PW 12 Dissolve in 2 mL of sulfuric acid solution (2 mol / L) and heat to 50°C, then slowly dropwise add it to the PVA-PEG solution obtained in step (1) and stir at 80°C for 2 hours to obtain PVA-PEG-PW 12 Solution;

[0059] (3) Dissolve 0.35 g of citric acid in 1 mL of deionized water and slowly add it dropwise to the PVA-PEG-PW obtained in step (2). 12 The solution was stirred at 80°C for 30 minutes and then the mixed solution was poured into a surface dish. The mold was then placed in a vacuum drying oven and dried at 50°C for 5 hours. After cooling, PVA-PEG-PW was obtained. 12 -3 hydrogel electrolytes, such as Figure 1 shown.

[0060] Example 4

[0061] (1) 4.0 g PVA and 1.3 g PEG were respectively dissolved in 10 mL sulfuric acid solution (2 mol / L), and then the two solutions were evenly mixed and heated to 80° C. to obtain 20 mL of PVA-PEG solution;

[0062] (2) 40 mg PW 12 Dissolve in 2 mL of sulfuric acid solution (2 mol / L) and heat to 50°C, then slowly dropwise add it to the PVA-PEG solution obtained in step (1) and stir at 80°C for 2 hours to obtain PVA-PEG-PW 12 Solution;

[0063] (3) Dissolve 0.35 g of citric acid in 1 mL of deionized water and slowly add it dropwise to the PVA-PEG-PW obtained in step (2). 12 The solution was stirred at 80°C for 30 minutes and then the mixed solution was poured into a surface dish. The mold was then placed in a vacuum drying oven and dried at 50°C for 5 hours. After cooling, PVA-PEG-PW was obtained. 12 -4 hydrogel electrolyte.

[0064] PVA-PEG-PW prepared in Example 3 12 Photo of hydrogel electrolyte Figure 1 As shown,

[0065] Figure 2 PVA-PEG-PW prepared in Example 3 12 SEM image of the hydrogel electrolyte. It can be seen from the figure that the hydrogel electrolyte presents a three-dimensional network structure ( Figure 2 a), and has a micron-scale cavity structure, about 10 μm in size ( Figure 2 b) It also provides channels for the diffusion movement of ions.

[0066] Figure 3 PVA-PEG-PW prepared in Example 3 12 EDS image of the hydrogel cross section. This image shows the distribution of phosphorus and tungsten, the main elements of the added phosphotungstate.

[0067] Preparation of PVA-PEG hydrogel:

[0068] (1) 4.0 g PVA and 1.3 g PEG were respectively dissolved in 10 mL sulfuric acid solution (2 mol / L), and then the two solutions were evenly mixed and heated to 80° C. to obtain 20 mL of PVA-PEG solution;

[0069] (2) Dissolve 0.35 g of citric acid in 1 mL of deionized water and slowly add it dropwise to the PVA-PEG solution obtained in step (1), stir at 80° C. for 30 minutes, and pour the mixed solution into a watch glass. Then, place the mold in a vacuum drying oven and dry it at 50° C. for 5 hours. After cooling, the PVA-PEG hydrogel electrolyte can be obtained.

[0070] PVA-PEG hydrogel and PVA-PEG-PW prepared in Example 1-4 12 The hydrogel electrolyte was assembled into a carbon-based flexible capacitor, and the gel electrolyte membrane and two activated carbon electrodes were assembled into a "sandwich-type" sandwich structure to test the electrochemical performance.

[0071] Figure 4 Carbon-based flexible capacitors assembled from PVA-PEG hydrogels prepared at 10 mV·s -1 CV curves and current density of 1 mA cm -2 The GCD curve under the condition that PW is not added 12 In the case of , the CV curve has no obvious polarization from 0 to 1.4V, showing good capacitance behavior, and the GCD curve shows a typical triangular shape, and the reversibility of the surface electrode reaction is good during the charge and discharge process. When the voltage window reaches 1.5V, a charging platform can be observed in the curve. The CV curve and GCD curve can be used to judge that when PW is not added 12 The maximum voltage window of the prepared gel electrolyte is 1.4V.

[0072] Similarly, we can get Figure 5 -PVA-PEG-PW prepared in Example 1 12 The maximum voltage window of the hydrogel is 1.5 V; Figure 6 -PVA-PEG-PW prepared in Example 2 12 The maximum voltage window of the hydrogel is 1.6 V; Figure 7 -PVA-PEG-PW prepared in Example 3 12 The maximum voltage window of the hydrogel is 1.7 V; Figure 8 -PVA-PEG-PW prepared in Example 4 12 The maximum voltage window of the hydrogel is 1.5V.

[0073] Fig. 9 Different PVA-PEG-PW prepared for Examples 1 to 4 12 Ionic conductivity diagrams and corresponding column distribution diagrams of hydrogels and PVA-PEG hydrogels, where Figure a is the ionic conductivity diagram and Figure b is the column distribution diagram.

[0074] The formula for ionic conductivity is:

[0075] Where d is the thickness of the hydrogel electrolyte, A is the area of ​​the hydrogel electrolyte, and R s is the ohmic resistance of the hydrogel electrolyte.

[0076] It can be seen from the figure that adding different quality PW 12 PVA-PEG-PW 12 The ionic conductivity of gel electrolyte increases first and then decreases. 12 When the amount reached 30 mg, the highest ionic conductivity was 51.7 mS·cm -1 .

[0077] Fig.10 To prepare PVA-PEG hydrogel and add different PW 12 Mass preparation of PVA-PEG-PW 12 The stress-strain curve of the hydrogel shows that the PVA-PEG-PW prepared in Example 3 12 -3 hydrogel can reach a maximum elongation at break of 996%, which improves the tensile properties of the gel.

[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various optimization schemes. Any modification, equivalent replacement and improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a hydrogel electrolyte with a wide voltage window by adjusting a polyacid, characterized in that The method comprises the following steps: (1) dissolving polyvinyl alcohol and polyethylene glycol in an acidic solvent to obtain a PVA-PEG mixed solution; (2) Dissolve phosphotungstic acid in an acidic solvent to obtain PW 12 Solution; (3) PW 12 The solution was slowly added dropwise to the PVA-PEG mixed solution, heated to 80-90°C and stirred at constant temperature to obtain PVA-PEG-PW 12 Solution; (4) Slowly add the citric acid aqueous solution to the PVA-PEG-PW 12 The solution was stirred and mixed, and the temperature was maintained at 80-90°C; the obtained solution was poured into a mold and vacuum dried to obtain PVA-PEG-PW 12 The hydrogel electrolyte is the hydrogel electrolyte with a wide voltage window.

2. The method according to claim 1, characterized in that The polyvinyl alcohol is PVA-1788, and the alcoholysis degree is 87-89%.

3. The method according to claim 1, characterized in that The molecular weight of the polyethylene glycol is 600-20000.

4. The method according to claim 1, characterized in that In the step (1), the mass ratio of the polyvinyl alcohol to the polyethylene glycol is 1:0.2-1.

5. The method according to claim 1, characterized in that In the step (2), the mass ratio of phosphotungstic acid to polyvinyl alcohol in the step (1) is 0.0025 to 0.015:

1.

6. The method according to claim 1, characterized in that The acidic solvent in step (1) and step (2) is a 1-3 mol / L sulfuric acid solution.

7. The method according to claim 1, characterized in that In the step (1), the volume amount of the acidic solvent is 2 to 10 mL / g based on the mass of the polyvinyl alcohol; and in the step (2), the volume amount of the acidic solvent is 30 to 250 mL / g based on the mass of the phosphotungstic acid.

8. The method according to claim 1, characterized in that In the step (4), the citric acid, PVA-PEG-PW 12 The mass dosage ratio of polyvinyl alcohol in the solution is 0.05-0.1:

1.

9. A hydrogel electrolyte with a wide voltage window prepared by the method according to any one of claims 1 to 8.

10. Use of the hydrogel electrolyte with a wide voltage window as claimed in claim 9 in preparing an all-solid-state supercapacitor.

Citation Information

Patent Citations

  • Phosphomolybdic acid-polymer composite conductive hydrogel, preparation method thereof and application of phosphomolybdic acid-polymer composite conductive hydrogel in all-solid-state flexible super capacitor

    CN110423348A

  • Polyacid-based electrolyte conductor material as well as preparation method and application thereof

    CN112151842A